Gramatical Cohesion and Lectical Cohesion in Text Report on Student Observation Results - Ainiyah Ekowati; Aceng Rahmat; Fathiaty Murtadho (STKIP Singkawang, 2019)
The use of cohesion in text can create relationships between elements of language in communication so that effective communication is created for language users. This study aims to describe the use of grammatical cohesion and lexical cohesion in the text of the report on the results of the observation of Indonesian Language and Literature Education Study Program at Pakuan University, Bogor. This study uses a descriptive and qualitative approach while the method used is the method proposed by Halliday and Hasan regarding cohesion. Based on the results of the research conducted, it was found that the use of grammatical cohesion in the form of references, substitutions, ellipsis and conjunctions, and lexical cohesion consisted of synonymy, hypernymy and collocation in the observation report text of Indonesian Language and Literature Education Study Program at Bogor Pakuan University.